Pediatric temporomandibular joint (TMJ) arthritis, an elusive complication of acute mastoiditis. (July 2022) - Cohen Atsmoni, Smadar; Hennedige, Anusha; Richardson, David; De, Sujata
Abstract: Introduction: Septic arthritis of the Temporomandibular joint (TMJ) is a rare complication of acute middle ear infection. Presentation is elusive and could be easily missed. Often diagnosis is made only with consequential development of TMJ ankylosis. This study intends to characterize patients and course of disease and suggest a diagnostic and therapeutic strategy. Methods: Retrospective review of all children diagnosed with TMJ arthritis and/or TMJ ankylosis secondary to acute middle ear infection, treated in a tertiary pediatric medical center between the years 2005 and 2021. Result: Seven patients were identified with otogenic TMJ arthritis. Median age at presentation was 1.14 years (IQ range 1.1–1.5). All seven were diagnosed with acute mastoiditis. CT scans demonstrated TMJ related collections in 5/7 and intracranial complications in 3/7. Treatment included cortical mastoidectomy for 5/7. One patient had a concomitant surgical washout of the TMJ. Two patients had drainage only of subperiosteal collections. Six of the seven patients went on to develop TMJ ankylosis that presented within a median of 2.8 years (IQ range 2.6–3.9) after the episode of acute mastoiditis. All six patients presented with trismus and facial growth anomalies, and all but one required surgery to release the ankylosis. Conclusion: Otogenic TMJ arthritis develops mostly in young children with acute mastoiditis and intratemproal and/or intracranial suppuration. Imaging is helpful in making the diagnosis, with TMJ related collections on CT being the most common finding. TMJ ankylosis can develop within a few years and present with trismus and abnormal facial growth. Cortical mastoidectomy does not seem to prevent ankylosis. It remains unclear whether focused treatment to the TMJ or physiotherapy could be beneficial in that.